Sistem Presensi Perkuliahan pada Universitas Kristen Petra Berbais RFID Dan Arduino - Edwin Prastyan Wiyanto; Andreas Handojo; Resmana Lim (Jurnal Infra, 2019)
Presence is a recording of student attendance in attending a course. With the presence of these records, especially for Petra Christian University, students can observe the number of attendance in each course. During this time the presence at Petra Christian University was done manually, namely with paper for signatures. There are several obstacles such as no data backup when the paper is lost, and too much paper usage. Therefore, another alternative is needed to reduce these obstacles.In this journal, a presence system will be created using RFID technology and Arduino which is connected to the presence website that can help students, lecturers, departments and BAAK in viewing attendance and processing the data.The final result of this journal is a tool that has been designed and a website to facilitate students and lecturers in presenting. In addition, presence data which is stored in the database can be processed by departments and BAAK.